Physicians' decision processes about the HPV vaccine: A qualitative study. Issue 3 (15th January 2021) - Bouchez, Maité; Ward, Jeremy K.; Bocquier, Aurélie; Benamouzig, Daniel; Peretti-Watel, Patrick; Seror, Valérie; Verger, Pierre
Highlights: Doctors' attitudes towards HPV vaccine depended on their trust in health authorities. The lower their trust in health authorities, the higher their hesitancy. The higher their hesitancy, the more importance they attached to patients' opinion. Even when favorable to HPV vaccine, they were more or less proactive with patients. This depended on their professional values regarding their public health role. Abstract: Background: The contemporary crisis of trust in vaccines has severely impaired acceptance of the HPV vaccine, especially in France, where its uptake culminated at 23.7% in 2018 (complete course at age 16). Physicians' recommendations strongly influence its acceptance/refusal. Our study sought to understand the decision processes leading physicians to recommend this vaccine (or not). Methods: Qualitative interviews of French physicians (general practitioners, gynecologists, and pediatricians). We first randomly selected doctors in a national register of medical professionals and then resorted to snowballing to build a convenience sample. We coded the interviews in a thematic analysis built both inductively and deductively from our research questions and data. Results: Two thirds of the participants (19/28) were favorable to HPV vaccination, some (4) opposed it, while the others were hesitant about recommending it. In explaining their opinions, most participants mentioned that they trusted the stakeholders within the vaccination system: the less trust they had, the more critical they were of the vaccine and the more importance they attributed to patients' opinions. We identified three different ways they interacted with patients on this topic: informing and convincing; adapting to patients' opinions; refusing compromise about vaccination. Crossing these various themes, we found 5 types of physicians: dissidents (mistrustful of the healthcare system and HPV vaccine), hesitant (finding it difficult to make up their minds about this vaccination), laissez-faire (letting patients decide by themselves, but very favorable to HPV vaccination), educator (very favorable), and uncompromising vaccinators (refusing debate). Pediatricians were overrepresented among the latter two types. Conclusions: Physicians' judgment was influenced by their trust in the stakeholders involved in designing and implementing the HPV vaccination strategy. In this sense, doctors did not differ substantially from laypeople. They were, nonetheless, strongly influenced by their professional style and ethos.